Political Connection and Corporate Performance: A Research Library - Balqis, Malika; Raharjo, Yulianti; Supratiwi, Wiwik (Budapest International Research and Critics University, 2022)
This study aims to review various literatures and get an overview related about political connection and corporate performance from a research library. This type of research is library research. This research uses various written sources such as articles, books, and other relevant documents. The main sources of information for articles used in this study are in the last 10 years, namely 2011 to 2020. This study uses online journal databases such as Scopus, Google Scholar, and Emerald to obtain literature from previous studies that are relevant to the topic of this research. The keywords used in the literature search process include political connection, firm performance, politically connected board, political connected in boardroom, and political connection and firm performance. Researchers conduct an analysis of how the relationship between the board of directors is connected to politics and the resulting company performance. The results show that companies that have political connections will receive a number of benefits and can help companies to improve their performance. These advantages include a lower cost of equity, much lower borrowing costs and interest, lower tax rates, and much better stock market performance.